Contextualising the pervasive impact of macroeconomic austerity on prison health in England: a qualitative study among international policymakers - Nasrul Ismail (BMC, 2019)
Abstract Background Prisons offer the state the opportunity to gain access to a population that is at particularly high risk of ill-health. Despite the supportive legal and policy structures surrounding prison rehabilitation, the oppressive nature of the austerity policy in England threatens its advanced improvement. Methods Using grounded theory methodology, this is the first interdisciplinary qualitative study to explore the impact of macroeconomic austerity on prison health in England from the perspective of 29 international prison policymakers. Results The far-reaching impact of austerity in England has established a regressive political system that shapes the societal attitude towards social issues, which has exacerbated the existing poor health of the prisoners. Austerity has undermined the notion of social collectivism, imposed a culture of acceptance among prison bureaucrats and the wider community, and normalised the devastating impacts of prison instability. These developments are evidenced by the increasing levels of suicide, violence, radicalisation and prison gangs among prisoners, as well as the imposition of long working hours and the high levels of absenteeism among prison staff. Conclusions This study underscores an important and yet unarticulated phenomenon that despite being the fifth largest economy in the world, England's poorest, marginalised and excluded population continues to bear the brunt of austerity. Reducing the prison population, using international obligations as minimum standards to protect prisoners' right to health and providing greater resources would create a more positive and inclusive system, in line with England's international and domestic commitments to the humane treatment of all people.